Cardiometabolic Benefits of Intermittent Fasting - Varady, Krista A; Cienfuegos, Sofia; Ezpeleta, Mark; Gabel, Kelsey (Annual review of nutrition, 2021)
This review aims to summarize the effects of intermittent fasting on markers of cardiometabolic health in humans. All forms of fasting reviewed here-alternate-day fasting (ADF), the 5:2 diet, and time-restricted eating (TRE)-produced mild to moderate weight loss (1-8% from baseline) and consistent reductions in energy intake (10-30% from baseline). These regimens may benefit cardiometabolic health by decreasing blood pressure, insulin resistance, and oxidative stress. Low-density lipoprotein cholesterol and triglyceride levels are also lowered, but findings are variable. Other health benefits, such as improved appetite regulation and favorable changes in the diversity of the gut microbiome, have also been demonstrated, but evidence for these effects is limited. Intermittent fasting is generally safe and does not result in energy level disturbances or increased disordered eating behaviors. In summary, intermittent fasting is a safe diet therapy that can produce clinically significant weight loss (>5%) and improve several markers of metabolic health in individuals with obesity.